2014
DOI: 10.1146/annurev-immunol-032713-120236
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Regulation of Immune Responses

Abstract: The immune system provides defense against pathogens and functions to maintain tissue homeostasis for the life of the organism. These diverse functions of immunity are bioenergetically expensive, requiring precise control of cellular metabolic pathways. Although the initial observations in this area were made almost a century ago, studies over the last decade have elucidated the molecular basis of how extracellular signals control the uptake and catabolism of nutrients in quiescent and activated immune cells. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
610
0
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 709 publications
(630 citation statements)
references
References 124 publications
(133 reference statements)
14
610
0
6
Order By: Relevance
“…During I/R, hypoxia, but also nutrient starvation, triggers injuries, as it might happen in our H/R model, which combines hypoxia and nutrient deprivation. It has been previously shown that glucose starvation can modulate DC functions (49). As such, we cannot exclude that the observed effects are partially mediated by nutrient starvation.…”
Section: Discussionmentioning
confidence: 78%
“…During I/R, hypoxia, but also nutrient starvation, triggers injuries, as it might happen in our H/R model, which combines hypoxia and nutrient deprivation. It has been previously shown that glucose starvation can modulate DC functions (49). As such, we cannot exclude that the observed effects are partially mediated by nutrient starvation.…”
Section: Discussionmentioning
confidence: 78%
“…While no changes were detected in the corticosterone levels (Figures S4A and S4B), the type 2 cytokines IL-4, IL-5, and IL-13 were markedly upregulated in both ingSAT and pgVAT of CR mice compared to the AL controls ( Figures 4A, S4C, and S4D). Eosinophils and the type 2 cytokines are sufficient to promote beige fat development through alternative activation of M2 macrophages expressing tyrosine hydroxylase (TH) (Ganeshan and Chawla, 2014;Lee et al, 2015;Martinez et al, 2009;Qiu et al, 2014), rate-limiting enzyme in the catecholamine biosynthesis (Nguyen et al, 2011). Indeed, Th mRNA and TH protein levels were increased in ingSAT and pgVAT in the CR mice ( Figures 4B and S4E).…”
Section: Decreased Caloric Uptake Enhances Type 2 Immune Responsementioning
confidence: 99%
“…Although originally defined in the context of host defense against parasitic helminths (3), M2 macrophages are now appreciated as being important orchestrators of inflammation resolution and metabolic homeostasis through their secretion of antiinflammatory cytokines (e.g., IL-10 and TGF-β), mediators of tissue repair (eg. collagen), and catecholamines (4). Moreover, monocyte-derived M2 macrophages were recently shown to be an important source of retinoic acid (5), a hormonelike metabolite that promotes the differentiation of immunosuppressive Tregs (6,7).…”
Section: Introductionmentioning
confidence: 99%